Al-Akhṭā’ An-Naḥwiyyah Laday Aṭ-Ṭulab Al-Mubtadi-in fī Al-Jāmi’ah Al-Islāmiyyah Al- ‘Ālamiyyah Malaysia - Agus Niamin; Radhwa Binti Abu Bakar (LISANUDHAD: JURNAL BAHASA, PEMBELAJARAN DAN SASTRA ARAB, 2019)
AbstractSyntactic (Naḥw) errors are the subjects of linguists’ debate that has long lasted without a fairly winning solution.  However, that solution should be still attempted particularly pertaining to linguistic, logical and syntactic corrections. It is this issue that the present study will deal with mainly in connection with some syntactic errors to which most writing errors have happened. The research will employ selected papers written by students of the International Islamic University Malaysia (IIUM) as the subject of analysis. The study’s result eventually reveals that syntactic aspect is one of the most frequently happened mistake among Malaysian universities particularly those who are the non-Arabic speaking beginners.Keywords: Grammatical Errors, Junior Students, Error Analysis, Arabic Grammar, Syntactic. الأخطاء النحوية لدى الطلاب المبتدئين في الجامعة الإسلامية العالمية ماليزيارضوى أبو بكر، أغوسني أمينالجامعة العالمية الإسلامية مالزياradhwa@iium.edu.my, agusniamin@gmail.comملخصالأخطاء النحوية قضية كبيرة الإشكالية وطويلة النقاش بين المتخصصين دون أن تصل إلى حلولها فعّالة. ومهما يكن الأمر، فالتصحيح اللغوي والإصلاح المنطقي مهمان لا نفر منهما. وإليهما نحتاج إلى تحليل تلك الأخطاء النحوية، لذلك جاء هذا البحث هدفا إلى التركيز على الأبواب النحوية التي كثرت فيها الأخطاء، وذلك بتطبيقها على المقالات المختارة من طلبة الجامعة العالمية الإسلامية بماليزيا. فمن خلال هذا البحث، أدرك الباحث أن الأخطاء النحوية وقعت بكثرة على كتابات ومقالات للطلبة المبتدئين  الناطقين بغير العربية في الجامعة بماليزيا.كلمات مفتاحية: الأخطاء النحوية، الطلاب المبتدئين، تحليل الأخطاء، قواعد اللغة العربية، النحو العربي